Effects of composition and density of nonwoven fabric on a soil-free growing medium. (October 2013) - Hsieh, Jing-Chzi; Lou, Ching-Wen; Lin, Ching-Wen; Chen, Jin-Mao; Lin, Jia-Horng
The practice of covering the roof of a building with a layer of living vegetation has many benefits. However, soil is heavy and most soil substitutes present special problems such as a tendency to block drains. Previous studies utilized a lightweight, soil-free growing medium that replaced actual soil to lessen the mechanical load on the roof. This study used a lightweight nonwoven fabric as a growing medium for living roofs. Two types of polyester fibers were blended at various ratios and then thermally dried into various densities. A desirable growing medium must resist moisture deformation and encourage root implantation. The results indicated that 0.030 g/cm 3 was the optimum density and that the weight of low-melting-point polyester fibers had to be in excess of 20 wt%. It was anticipated that the manufacturer who adjusts factory parameters to benefit from this research will reduce the production cost.